Pengaruh Insentif, Kepemimpinan dan Budaya Organisasi terhadap Semangat Kerja Karyawan pada PT. Sung Hyun Indonesia di Pasuruan - Mashudi Mashudi; Muhammad Yani; Dhinda Meidita Setiandayani (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2018)
This study aims to determine whether significant incentives, leadership, and organizational culture to employee morale. And to know whether the inter-variable incentives, leadership, and organizational culture that has the most significant effect on employee morale. This research method is quantitative method. The analysis technique used in this research is multiple linear regression analysis using SPSS (Statistical Program for Social Science) version 16 for windows. The results obtained based on the validity test show all existing questions are valid. To test the reliability of all variables. Partial research results show the role, spirit and spirit of the organization. The simultaneous test results show that the spirit, leadership and organizational culture have a simultaneous influence on employee morale, and leadership variables have the most significant effect on employee morale because of the greatest .and least significance compared to other independent variables. Variable incentives, leadership and organizational culture have strong relationships and have an effect on employee morale.